A Dynamic Kinetic Resolution Approach to Axially Chiral Diaryl Ethers by Catalytic Atroposelective Transfer Hydrogenation. Issue 7 (11th January 2023) - Dai, Linlong; Liu, Yuheng; Xu, Qing; Wang, Meifang; Zhu, Qiaohong; Yu, Peiyuan; Zhong, Guofu; Zeng, Xiaofei
Abstract: Diaryl ethers are widespread in biologically active compounds, ligands and catalysts. It is known that the diaryl ether skeleton may exhibit atropisomerism when both aryl rings are unsymmetrically substituted with bulky groups. Despite recent advances, only very few catalytic asymmetric methods have been developed to construct such axially chiral compounds. We describe herein a dynamic kinetic resolution approach to axially chiral diaryl ethers via a Brønsted acid catalyzed atroposelective transfer hydrogenation (ATH) reaction of dicarbaldehydes with anilines. The desired diaryl ethers could be obtained in moderate to good chemical yields (up to 79 %) and high enantioselectivities (up to 95 % ee ) under standard reaction conditions. Such structural motifs are interesting precursors for further transformations and may have potential applications in the synthesis of chiral ligands or catalysts. Abstract : A dynamic kinetic resolution approach was developed for the synthesis of axially chiral diaryl ethers via a Brønsted acid catalyzed atroposelective transfer hydrogenation (ATH) reaction of dicarbaldehydes with anilines. The chiral phosphoric acid catalyzed dynamic kinetic resolution strategy has provided a modular platform for the synthesis of axially chiral diaryl ethers.